2014
DOI: 10.1590/s1984-29612014035
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem hemoparasite detection in free-living Brazilian brown brocket deer (Mazama gouazoubira, Fischer 1814)

Abstract: Post-mortem hemoparasite detection in free-living Brazilian brown brocket deer (Mazama gouazoubira, Fischer 1814) AbstractTick-borne infections can result in serious health problems for wild ruminants, and some of these infectious agents can be considered zoonosis. The aim of the present study was the post-mortem detection of hemoparasites in free-living Mazama gouazoubira from Minas Gerais state, Brazil. The deer samples consisted of free-living M. gouazoubira (n = 9) individuals that died after capture. Necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In Minas Gerais state observation of A. phagocytophilum has been increasing in animals (Silveira et al 2014 and recently, the present study group detected a dog with Ehrlichia canis and A. phagocytophilum co-infection in the city of Belo Horizonte. Lethargy and skin lesions were the clinical signs observed and abnormal hematological parameters such as severe thrombocytopenia were the most important laboratorial alterations .…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In Minas Gerais state observation of A. phagocytophilum has been increasing in animals (Silveira et al 2014 and recently, the present study group detected a dog with Ehrlichia canis and A. phagocytophilum co-infection in the city of Belo Horizonte. Lethargy and skin lesions were the clinical signs observed and abnormal hematological parameters such as severe thrombocytopenia were the most important laboratorial alterations .…”
Section: Introductionsupporting
confidence: 53%
“…In Brazil, the bacterium has been detected by molecular methods in dogs (Santos et al 2011, in carnivorous birds ) and in brown brocket deer (Mazama gouazoubira) (Silveira et al 2014); and in horses (Salvagni et al 2010) and Brazilian marsh deer (Blastocerus dichotomus) (Sacchi et al 2012) by serological methods. In Minas Gerais state observation of A. phagocytophilum has been increasing in animals (Silveira et al 2014 and recently, the present study group detected a dog with Ehrlichia canis and A. phagocytophilum co-infection in the city of Belo Horizonte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that there may be possibly a closely related species but not the same as A. phagocytophilum-like agent circulating in Colombia. Although A. phagocytophilum has already been detected in dogs (SANTOS et al, 2011 and brown brocket deer (SILVEIRA et al, 2014) in Brazil, previous reports also have found new genotypes of Anaplasma spp. phylogenetically similar to A. phagocytophilum in wild carnivores kept in captivity in zoos , wild birds and in cats (ANDRÉ et al, 2014) in Brazil, corroborating with the findings of the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Several reports have been published about the occurrence of these agents in South America (DAGNONE et al, 2009;MACHADO et al, 2012;SACCHI et al, 2012;SALVAGNI et al, 2010;SANTOS et al, 2009SANTOS et al, , 2011SANTOS et al, , 2013SILVEIRA et al, 2014;ANDRÉ et al, 2012ANDRÉ et al, , 2014. In Colombia, although a 20% seroprevalence to A. phagocytophilum has been found among rural workers in the country's northern region, the agent has not yet been characterized molecularly in mammals (MÁTTAR & PARRA, 2006).…”
Section: Introductionmentioning
confidence: 99%